Investigating the Factors Affecting Speeding Violations in Jordan Using Phone Camera, Radar, and Machine Learning - Al-Mistarehi, Bara’ W.; Alomari, Ahmad H.; Imam, Rana; Alnaasan, Tasneem K. (Frontiers in Built Environment, 2022)
Traffic accidents are considered the leading cause of death for the age group (5–29). They cause approximately 1.3 million deaths every year. Different factors cause traffic accidents; one of them is speeding violations. This work studied speeding violations and the factors that affect them in Irbid, Jordan. Several factors related to the driver, environment, vehicle, road, and weather conditions were studied. The analysis results showed that age, vehicle type, speed limit, day of the week, season, accident year, accident time, license category, and light condition affect speeding violations. To be more specific, young drivers, morning rush hours, clear visibility during daylight, the winter season, slippery roads (due to rain, snow, or ice at low temperatures), and a speed limit of 40 km/h in residential areas; were all associated with a high percentage of speeding violations. Seven hot spots for speeding violations in Irbid were specified, and the free flow speed was measured using the radar and video at these hot spots. The 85th percentile speed was estimated, and the results for all locations were less than the speed limit. In addition to that, the radar and video measurements were compared to specify the most accurate method. The results did not show any difference between the measurements.